2015
DOI: 10.1353/cpr.2015.0060
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Faith-Based Stress Management Intervention in a Rural African American Community

Abstract: Background Faith-based mental health interventions developed and implemented using a community-based participatory research (CBPR) approach hold promise for reaching rural African Americans and addressing health disparities. Objectives To describe the development, challenges, and lessons learned from the Trinity Life Management, a faith-based stress management intervention in a rural African American faith community. Methods The researchers used a CBPR approach by partnering with the African American faith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This suggests that other strategies must be employed. 32 However, an alternative approach that employed the concept of a trusted source included ~1,003 Black churches, each setting a recruitment goal based on church attendance. Serving as recruiters, a pastor and a church member shared study information with the congregation and received monetary incentives upon returning the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that other strategies must be employed. 32 However, an alternative approach that employed the concept of a trusted source included ~1,003 Black churches, each setting a recruitment goal based on church attendance. Serving as recruiters, a pastor and a church member shared study information with the congregation and received monetary incentives upon returning the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…While Black’s average scores for trust in religious organizations were near the midpoint of the scale, indicating only moderate levels of trust, our unadjusted and adjusted findings showed that Blacks had higher levels of trust in religious organizations compared to Whites, Asians and Pacific Islanders, and Others. Previous research shows that faith-based organizations and institutions may serve as credible sources of health information and resources for Blacks (Bryant, Moore, Willis, & Hadden, 2015; Sattin et al, 2016; Tanner et al., 2016; Tettey, Duran, Andersen, & Boutin-Foster, 2016). Our findings add to the literature by showing that compared to other racial/ethnic groups, Black respondents display higher levels of trust in religious organizations in specifically providing tobacco health information.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel line of work is exploring ways that congregational leadership may develop programmatic strategies for the transmission of health-related messages emphasizing sexual health and regular health screening (Brown and Cowart 2018; Powell et al 2017; White et al 2020). Additionally, several studies have highlighted the mental health benefits that accrue to members of disadvantaged communities, often persons of color, who are able to access faith-based support systems (Bryant et al 2014; Bryant et al 2015; Taylor et al 2000; Williams et al 2014). Continuing the focus on aging populations, Krause and Hayward (2012) have provided evidence of positive associations between pastoral emotional support, beliefs in God's ability to alleviate personal burdens and a greater sense of hopefulness in late life.…”
Section: Literature and Hypothesesmentioning
confidence: 99%